واقع تدریس مقرر أخلاقیات المعلومات فی أقسام علوم المعلومات بالجامعات الحکومیة السعودیة: دراسة وصفیة تحلیلیة - د. احمد فرج أحمد (المجلة الدولية لعلوم المكتبات والمعلومات)
This study focuses on the description and analysis of the current status ofteaching information ethics and legislation course at the curriculum of InformationScience Departments at Saudi governmental universities. The researchmethodology used is the descriptive and analytical approach and represented thefundamental tools such as the questionnaire, personal correspondence inaddition to applying the content analysis method.The study attempts to provide indicators resulting from the analysis andevaluation of the course to explore the different ways the develop it notably:disclosure of the course status in the curriculum of academic departments, andindicate the effectiveness of the teaching methods used, and analysis of coursedescription to recognize the goals and learning outcomes with the currentdevelopment trends of these departments, in addition to exploring the obstaclesto the achievement of its objectives and proposed solutions to overcome them.And try to clarify the impact of this course on the enhancing of informationbehaviors for staff members